Digitalization of the Labor Market - Botirovich, Mirzahodjaev Alisher (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
In the context of digitalization, it is important to determine the characteristics of the labor market. This is because identifying the impact of digitalization on the labor market, highlighting its pros and cons, and eliminating the risk to labor relations provide an opportunity to address the unemployment caused by digitalization.